SOME IMPACTS OF ARMED CONFLICT ON AGRICULTURE: A CASE STUDY FROM SOUTH WOLLO, NORTHEASTERN ETHIOPIA - Seid, Ali; Asresie, Aleme; Muhie, Seid Hussen; Hassen, Seid (Chilean Journal of Agricultural & Animal Sciences, 2024)
The Ethiopian agriculture sector, supporting over 85% of the population's livelihood, has been severely impacted by armed conflict, disrupting nearly every element of its value chain. Key direct impacts of conflict include the destruction of essential assets like farmland, livestock, crops, seed reserves, and critical infrastructure. This study aims to evaluate the war’s effect on agricultural inputs, management practices, and services in selected districts within South Wollo, northeastern Ethiopia, and to propose viable mitigation strategies. Both primary and secondary data were gathered, with primary data collected through surveys, focus group discussions, and interviews with key informants. Quantitative data were analyzed using SAS software, while qualitative data were examined through descriptive and narrative methods. The conflict has damaged agricultural inputs, management practices, infrastructure, and services, including irrigation canals, farmer training centers, veterinary services, and nursery sites, significantly exacerbating food insecurity. Agrochemical supplies were impacted for 53% of respondents, while 66.5% reported disruption in livestock management practices. Total irrigation infrastructure and agricultural institution damage in South Wollo was estimated at 17,988.90 million Ethiopian birrs (ETB). Therefore, immediate actions for the restoration of damaged agricultural infrastructures, institutions, and services are necessary, along with reinstating agricultural inputs, capacity building and community engagement, monitoring and evaluation, and networking and partnerships. These recommendations should be tailored based on the local context, existing conditions, and available resources. Engaging with communities to understand their unique needs and preferences is essential in making these initiatives effective and sustainable.